(untitled) (Brazilian Journal of Health Research, 2022)
Introduction: Preparing to enter university life through the entrance exam is an extremely stressful process in student life, surrounded by intense cognitive and emotional demands. Currently, there are tensions, uncertainties and challenges imposed by the current pandemic, based on the mental health of students. Objectives: Considering the possible consequences of the pandemic on increased anxiety, the project aimed to investigate the impacts of the current scenario on the daily lives of high school graduates enrolled in an educational institution in the metropolitan region of Belém, in 2020. Methods: This is a descriptive, cross-sectional study, with a quantitative approach, and using two instruments applied in the online format, including the State-Trait Anxiety Inventory (STAI). Results: The findings showed a prevalence of the mean level of anxiety, both trait (mean 48.6 ± 6.3 points) and state (mean 47.7 ± 6.4 points), with a significant association between the impact on sleep and the motivation for the study. However, there was no statistical association with state-trait anxiety, regarding sociodemographic variables and intended course. Conclusion: The pandemic significantly impacted the lives of students, with repercussions on mental health. As this is a period that precedes the entrance exam, prevention and support measures for health problems are necessary, given the problems faced as a result of the pandemic scenario.